Let f ( x ) be a function such that the system of equations below holds true for all x .
⎩ ⎨ ⎧ f ( − x ) + f ( 1 − x ) = 1 5 f ( 1 + x ) = 5 + f ( − x )
Find f ( x ) + f ( − x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( − x ) + f ( 1 − x ) = 1 5 , so if − x = y , f ( y ) + f ( 1 + y ) = 1 5 .
It is same as f ( x ) + f ( 1 + x ) = 1 5
1 5 = f ( x ) + ( 5 + f ( − x ) ) , f ( x ) + f ( − x ) = 1 5 − 5 = 1 0
Problem Loading...
Note Loading...
Set Loading...
Plug − x into the second equation to get f ( 1 − x ) = 5 + f ( x ) .
Now substitute this into the first equation: f ( − x ) + 5 + f ( x ) = 1 5 ⟹ f ( x ) + f ( − x ) = 1 0 .